KAJIAN EFEKTIVITAS DAN DINAMIKA KELOMPOK TERHADAP ADOPSI BUDIDAYA SAYURAN ORGANIK DI DESA PULUTAN WETAN, WONOGIRI - SUTARNO SUTARNO (JURNAL ILMIAH AGRINECA, 2015)
This study is about the effectiveness of farmer group dynamic to adopting organic vegetables cultivation and the relationship between the dynamic and the influence of effectiveness of farmer group towards adopting the organic vegetable cultivation. The study was carried out using an approach integrating the quantitative and qualitative research in the basic information about the context, subject and scale construction. The result of the study shows that knowledge is significantly different from adopting level, while personal interest and capability are not significantly different.Â  Technology will quantitatively as well as qualitatively support farmers to seek more information before they step forward to adopting level. Key words: effectiveness, dynamic, adopting Â